PERAN ADVOKAT PEMBERI BANTUAN HUKUM DALAM SISTEM PERADILAN PIDANA - Sri Wulandari (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2014)
One of the most fundamental rights of human life is the right to justice. Justice is the most noble of human interest in the criminal justice process because often violations of human rights that takes the role of lawyers in providing legal assistance to a suspect / defendant as the provisions of Law No. 8 of 1981 (Criminal Code) and Law No. 18, 2003 (Advocate). The job of an advocate is to serve the purposes of the law of his client / applicant for justice, the rule of law to perform well and do not let one in applicability. As the performance wujut responsibility placed on an anvil